Nephroprotective Effect of the Herbal Composition BNO 2103 in Rats with Renal Failure - Sergii K. Shebeko; Vladyslava V. Chernykh; Kateryna O. Zupanets (MDPI AG, 2020)
(1) Background: this research aims at studying the nephroprotective properties of BNO 2103 in a model of chromate-induced renal failure in rats and at proving the possibility of using BNO 2103 in clinical practice for the complex treatment of chronic kidney disease (CKD). (2) Methods: fifty rats divided into five groups were studied. The drugs BNO 2103, Prednisolone and Lespephril were administered within 20 days. The excretory function and the functional state of kidneys, blood biochemical parameters and indicators of nitrogen metabolism were determined. (3) Results: under the influence of BNO 2103, there was a significant improvement in renal excretory function, in nitrogen metabolism and blood biochemical parameters compared with the control pathology group. BNO 2103 also outperformed the comparators in most indicators. (4) Conclusions: BNO 2103 has demonstrated nephroprotective, hypoazotemic and diuretic effects; and can be used to implement to the combined therapy of CKD.